Универсальные селектирующие контуры измерительной системы разнотипных пространственных гармоник магнитного поля - Гетьман, Андрей Владимирович (НТУ "ХПИ", 2008)
Исследуются практические аспекты пространственного гармонического анализа с целью приближения к поверхности технических объектов области, доступной для аналитического описания внешнего магнитного поля. Теоретически обоснована пространственная конфигурация селектирующих контуров систем измерения сферических и сфероидальных гармоник магнитного поля. Обобщена методика применения контурных измерительных систем для определения амплитудных коэффициентов разнотипных гармоник скалярного магнитного потенциала.

The practical aspects of a spatial harmonic analysis are investigated with the purpose of approach to a surface technical objects of area, accessible to analytical description of an exterior magnetic field. The spatial configuration of systems contours of measuring spherical and spheroid harmonics of a magnetic field is theoretically justified. The procedure of application contour measuring systems for definition amplitude coefficients of varied harmonics of scalar magnetic potential is extended.
Universal selected contours of a measuring system of varied space harmonics of a magnetic field
Keywords: магнитное поле; селектирующие контуры; измерительная система; сферические гармоники; magnetic field; spatial harmonics; magnetic potential; spherical harmonic analysis